An Update on CARD Only Proteins (COPs) and PYD Only Proteins (POPs) as Inflammasome Regulators - Devi, Savita (Int J Mol Sci, 2020)
Inflammasomes are protein scaffolds required for the activation of caspase-1 and the subsequent release of interleukin (IL)-1β, IL-18, and danger signals, as well as the induction of pyroptotic cell death to restore homeostasis following infection and sterile tissue damage. However, excessive inflammasome activation also causes detrimental inflammatory disease. Therefore, extensive control mechanisms are necessary to prevent improper inflammasome responses and inflammatory disease. Inflammasomes are assembled by sequential nucleated polymerization of Pyrin domain (PYD) and caspase recruitment domain (CARD)-containing inflammasome components. Once polymerization is nucleated, this process proceeds in a self-perpetuating manner and represents a point of no return. Therefore, regulation of this key step is crucial for a controlled inflammasome response. Here, we provide an update on two single domain protein families containing either a PYD or a CARD, the PYD-only proteins (POPs) and CARD-only proteins (COPs), respectively. Their structure allows them to occupy and block access to key protein–protein interaction domains necessary for inflammasome assembly, thereby regulating the threshold of these nucleated polymerization events, and consequently, the inflammatory host response.